World history : the human experience - Farah, Mounir A. (Glencoe/McGaw- Hill, 1999)
The rise of civilizations; Flowering of civilizations; Regional civilization; Emergence of the modern world; Age of revolution; Industry and nationalism; World in conflict; The contemporary world.